Pemanfaatan material fasa berubah untuk mempertahankan kesegaran sayuran - Muhammad Irsyad; Natal Andreas H L Tobing; M Dyan Susila (TURBO [Tulisan Riset Berbasis Online], 2020)
Indonesia is an agricultural country with a tropical climate. One of the many agricultural products in Indonesia is vegetables. Handling of vegetables after harvesting is important because the decrease in product quality can reach up to 50%. This decrease in quality is the result of metabolic processes such as transpiration and respiration that occur in post-harvest vegetables. The respiration rate of vegetables cannot be stopped but can be slowed down by lowering the temperature, so that the freshness of the vegetables can last longer. One method of maintaining the temperature of vegetables is storage in a cool box with cooling media. Phase change material (PCM) is an alternative cooling medium that utilizes latent heat in thermal energy storage. Paraffin is a PCM that can be used for this application. Paraffin has a freezing and melting temperature range that can be adjusted according to your needs, namely by mixing liquid paraffin and solid paraffin. This study used mixed paraffin with a liquid-solid paraffin ratio of 98:2 mass basis. This mixture has a melting temperature of 6o C until 13 C and is close to the optimal temperature for storing vegetables, which is 5o C. In this study, testing was also carried out using water as a comparison. The test results show that ice can make vegetables last longer in cold conditions, namely that it is able to maintain the vegetable temperature below 20o C for 11 hours, while paraffin only lasts 2 hours. The physical condition of the vegetables that are cooled with ice in the packing changes color and becomes watery because the water in the vegetables is condensed. Meanwhile, on cooling with paraffin it is physically fresher.Keywords: PCM, paraffin, cool box, fresh vegetable storage